Seeking asylum in the UK: lesbian perspectives - Bennett, C; Thomas, F (Refugee Studies Centre, University of Oxford, 2013)
Many aspects of the UK asylum process can be confusing, disempowering and traumatic for lesbian asylum seekers. Recent research examines the impacts of this process on their experiences, their identity and their well-being.